A relationship of CO2 emission with economic growth, production in manufacturing sector and energy consumption from road sector in Malaysia - Duasa, Jarita; Ab. Rashid, Nur Fakhrina (Universiti Teknologi MARA, 2015)
This study attempts at empirically examine the relationships between CO2 emission with economic growth, road sector energy use and manufactured product in Malaysia. Using the bound testing approach to cointegration and error correction model developed within an autoregressive distributed lag (ARDL), we investigate whether a long-run equilibrium relationship exists between energy consumption from the two sectors, economic growth and CO2 emission. Results of the long-run model show a positive and significant relationship between road sector energy use and CO2 emission. This is consistent with our priori that postulates increase in energy consumption from the transportation will increase CO2 emission.